Loop-mediated isothermal amplification and its limit of detection for diagnostics of plant pathogens - Govindan Muthukumar; Ayyanar Kamalakannan; Irudhayasamy Johnson; Pachamuthu Kamaraj; Iyyamperumal Muthuvel; Shanmugam Varanavasiappan (Plant Protection Science)
Phytopathology deals with a branch of biology encompassing pathogens that infect plants. Pathogenic fungi, bacteria, viruses, viroids, and phytoplasmas are notorious and hard to control; preventive measures are important for managing disease as early as possible. Age-old management practices are time-consuming and labour-intensive processes. In the past, nucleic acid-based methods, such as hybridization, amplification, and sequencing, have been used extensively for the preliminary identification of plant pathogens. Recently, PCR-based methods have been widely used for the detection of plant pathogens. However, PCR methods are time-bound and require high-quality DNA extraction because of inhibitors' effects on PCR sensitivity. Several isothermal detection techniques are commonly used for the onsite detection of plant pathogens. Among them, loop-mediated isothermal amplification (LAMP) is a paradigm diagnostic tool for early plant pathogen detection. Hence, in this review, we discuss the rapid, reliable, sensitive method of the LAMP assay and the limit of detection (LOD) in different sectors of plant pathology. We also address the advantages and disadvantages of different LAMP approaches and future prospects.